Taxes or Fees? The Political Economy of Providing Excludable Public Goods - Kurtis J. Swope; Eckhard Janeba (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper provides a positive analysis of public provision of excludable public goods financed by uniform taxes or fees. Individuals differing in preferences decide using majority-rule the provision level and financing instrument. The median preference individual is the decisive voter in a tax regime, while an individual with preferences above the median generally determines the fee in a fee regime. Numerical solutions indicate that populations with uniform or left-skewed distributions of preferences choose taxes, while a majority coalition of high and low preference individuals prefer fees when preferences are sufficiently right-skewed. Public good provision under fees exceeds that under taxes in the latter case.
Keywords: 330; excludable public goods; public provision; voting